The international face of sports science through the window of the Journal of Sports Sciences - with a special reference to kinanthropometry - Reilly, T. (Journal of Sports Sciences, 2008)
The history of the Journal of Sports Sciences is traced from the antecedents of its initiation to the current time. The developments of the sports sciences at large are reflected in the content of the journal. Its links with the international agenda are described, and related to landmark publications. Special attention is given to the relationships with international bodies, the International Society for Advancement of Kinanthropometry and the World Commission of Science and Sports. The expansion of sport and exercise sciences, both nationally and internationally, was reflected in the increased frequency of publication of the journal. Key areas in the kinanthropometric content are identified and placed in context. The review culminates in the highlighting of likely areas for future research.